Peripheral dentinogenic ghost cell tumor of the ethmoid sinus: A case report - Liu, Guo (Medicine (Baltimore), 2020)
RATIONALE: The dentinogenic ghost cell tumor (DGCT), a locally invasive benign neoplasm, is one of the rarest odontogenic tumors, usually developing in the maxilla or mandible. It can be classified into 2 types: intraosseous (central) and extraosseous (peripheral). Here, we describe the first case of a peripheral DGCT located in the ethmoid sinus. PATIENT CONCERNS: An 8-year-old boy presented to our department with a longer than 7-month history of nasal obstruction, purulent secretion, and reduction in sense of smell in the right nasal cavity. DIAGNOSIS: The patient was diagnosed with peripheral DGCT of the ethmoid sinus based on computed tomography scan and pathology. INTERVENTIONS: Functional endoscopic sinus surgery was performed. OUTCOMES: With 2 years of follow-up, there was no evidence of recurrence. LESSONS: Peripheral DGCT can occur in the paranasal sinus and the need to consider this entity as a possible diagnosis by the clinicians.